Nesfatin-1 Receptor: Distribution, Signaling and Increasing Evidence for a G Protein-Coupled Receptor – A Systematic Review - Rupp, Sophia Kristina; Wölk, Ellen; Stengel, Andreas (Frontiers in Endocrinology, 2021)
Background Nesfatin-1 is an 82-amino acid polypeptide, cleaved from the 396-amino acid precursor protein nucleobindin-2 (NUCB2) and discovered in 2006 in the rat hypothalamus. In contrast to the growing body of evidence for the pleiotropic effects of the peptide, the receptor mediating these effects and the exact signaling cascades remain still unknown. Methods This systematic review was conducted using a search in the Embase, PubMed, and Web of Science databases. The keywords “nesfatin-1” combined with “receptor”, “signaling”, “distribution”, “pathway”, g- protein coupled receptor”, and “binding” were used to identify all relevant articles reporting about potential nesfatin-1 signaling and the assumed mediation via a Gi protein-coupled receptor. Results Finally, 1,147 articles were found, of which 1,077 were excluded in several steps of screening, 70 articles were included in this systematic review. Inclusion criteria were studies investigating nesfatin-1’s putative receptor or signaling cascade, observational preclinical and clinical studies, experimental studies, registry-based studies, cohort studies, population-based studies, and studies in English language. After screening for eligibility, the studies were assigned to the following subtopics and discussed regarding intracellular signaling of nesfatin-1 including the potential receptor mediating these effects and downstream signaling of the peptide. Conclusion The present review sheds light on the various effects of nesfatin-1 by influencing several intracellular signaling pathways and downstream cascades, including the peptide’s influence on various hormones and their receptors. These data point towards mediation via a Gi protein-coupled receptor. Nonetheless, the identification of the nesfatin-1 receptor will enable us to better investigate the exact mediating mechanisms underlying the different effects of the peptide along with the development of agonists and antagonists.